Keabsahan Visum Et Repertum dan Visum Psikiatrikum sebagai Alat Bukti dalam Penanganan Tindak Pidana Pemerkosaan - Werembinan, Petrus Carol; Cahyo Nugroho, Widhi (Journal Evidence Of Law, 2024)
This research aims to determine the legal strength of Visum et Repertum and Visum Psikiatrum as evidence in rape cases. Essentially, rape is an unlawful act, and criminal law classifies it as a criminal offense (rechtsdelicten). This study uses literature as its primary material, referred to as normative legal research or library research. The role of expert testimony in relation to the completeness of evidence in legal documents examined in court is very useful in enhancing the judge's confidence in the decision-making process. Visum et Repertum is considered a reliable form of evidence provided by a sworn doctor in criminal cases. The evidentiary status of Visum et Repertum in criminal cases is classified as documentary evidence under Article 184 paragraph (1) letter c and Article 187 letter c of the Indonesian Criminal Procedure Code, with expert testimony as per Article 1 number 28 of the Criminal Procedure Code and Stb 1937-350, along with Article 184 paragraph (1) letter b of the Criminal Procedure Code. The results of this research indicate that Visum et Repertum has legal strength as evidence in rape cases, as regulated under Article 184 paragraph (1) and Article 187 letter c.